2020
DOI: 10.1039/c9ra07607g
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities in the recovery of gold from electronic waste

Abstract: Rapid global technological development has led to the rising production of electronic waste that presents both challenges and opportunities in its recycling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
114
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(114 citation statements)
references
References 100 publications
0
114
0
Order By: Relevance
“…The HNO 3 favors the formation of trivalent gold ions, which further react with chloride to form tetrachloroaurate anions, according to Eq. (12) [21,43]. The aqua regia leaching is mostly used for alloys with high gold content [36].…”
Section: Aqua Regia Leachingmentioning
confidence: 99%
“…The HNO 3 favors the formation of trivalent gold ions, which further react with chloride to form tetrachloroaurate anions, according to Eq. (12) [21,43]. The aqua regia leaching is mostly used for alloys with high gold content [36].…”
Section: Aqua Regia Leachingmentioning
confidence: 99%
“…Not only is gold a common precious metal in jewels and coins, it is also employed increasingly within modern industries such as telecommunications, nanotechnology, chemical synthesis, and medicine. As a result, world demand for gold continues to increase which raises interest in developing new methods of extracting it from the earth or recovering it from societal waste streams [1, 2] . In addition, there is a growing need for advanced materials that are comprised of gold‐containing nanocomposites with nanoscale architecture [3, 4] .…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 40% of the world's tantalum production is used in this application, but its recycling is limited, at only 1% [1]. This is surprising, as electronic waste (e-waste) is becoming one of the fastest growing waste categories worldwide [2,3]. Furthermore, it was found that metal recovery from secondary resources is gradually becoming more cost-effective than virgin mining, especially as the volume of e-waste is projected to increase substantially; over the next few decades, new technologies will become cheaper and more accessible, driving up the rate of device obsolescence [4,5].…”
Section: Introductionmentioning
confidence: 99%